Community Service in Developing Basic English With Various Activities in Pekan Seruway Village - Raihana, Ariqqah; Benni Ichsanda Rahman; Fakhrurrazi; Dakiani; Nabila; Dela Wahyuni; Rosa Anjani; Elvida Futri Mahara; Nurul Hidayah Lubis; Rizki Tiara Ayunda; Pratiwi Hawa; Rasid Saleh Matondang; Raja Basya Turnip (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The community service work programme in Pekan Seruway Village carried out by group 3 from the UINSU Campus, Department of Tadris English, which carried out several activities to develop basic English for school children and also carried out several activities with the Seruway Village community. As for some of the activities, namely: EFL (English Fun Learning) which is learning English by playing games with the theme of vocabulary in English with the intention of honing the skills of children at SMP N 1 Seruway, The process of teaching basic English such as adding vocabulary, ice breaking, how to pronounce each vocabulary greetings and also introductions, Workshop with ibu datuk which discusses Pekan Seruway Village, Seminars with the theme of introducing the UINSU campus discussing each department and faculty, Hydroponics, English Film Review, Handicraft which is handicraft for junior high school children, Tadarus with the children of the Pekan Seruway village community, Healthy Life which is afternoon exercise and Studies or conducting Muharram activities with the community and male students of Al-Fuad pesantren. This Work or Service Programme is not only focused on one goal but we also build a family to approach the surrounding community.